One Step Towards: The Synthesis of Optimized Coumarin Derivatives as an Anti-HIV Agent - Kumar, Vikas; Pandey, Indra Prashad; Jain, Jainendra; Tripathi, Ram Babu (Indian Journal of Pharmaceutical Education and Research, 2019)
The development for the sustainable approach was a key ingredient for the research, especially in the field of drug development against HIV. Several attempts have been made in the positive direction for the treatment of fatal disease, however the suitable lead was missing in the therapeutically arena. Many different kinds of natural products, including coumarins, have been found to be active in the various anti-HIV models and still investigation is undergoing. The present finding demonstrates the synthesis of the best fit compound, which was revealed in the previously published research. The insilico study is further justified with the synthetic approach and their characterization. The in-silico based optimized coumarin structure have been tried to get closer to the drug discovery process, where in the future it will be evaluated for the in-vitro / in-vivo biological screening to get the lead molecule for the treatment of HIV. The objective of this research is to evaluate data on coumarins’ potent activity with respect to the inhibition of HIV-reverse transcriptase; Structural modification is a powerful tool to increase the potential of bioactive principles. By applying scientific expertise and modern scientific technology, new single compounds will assuredly be developed as potent antiHIV candidates for world-class new drug development.
Keywords: Coumarins; HIV integrase inhibitors; Protease inhibitors; Reverse transcriptase; inhibitors; QSAR